1996
DOI: 10.1002/macp.1996.021970608
|View full text |Cite
|
Sign up to set email alerts
|

Swelling behavior and controlled release of new hydrolyzable poly(ether urethane) gels derived from saccharide and L‐lysine derivatives and poly(ethylene glycol)

Abstract: New hydrolyzable gels bearing saccharide, L-lysine, and poly(oxyethy1ene) moieties were prepared via polyaddition of methyl ~-~-glucofuranosidurono-6,3-lactone (1) and poly(ethy1ene glycol) (PEG, M, = 1000) with an L-lysine derivative, methyl (S)-2,6-diisocyanatohexanoate (2), using dibutyltin dilaurate and triisocyanate 3 as a catalyst and a crosslinking agent, respectively. The swelling ratio and rate of hydrolysis of these gels in phosphate buffers increased with the content of PEG. Hydrolysis of these gels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…In general, the amount of absorbed water was lower for the more hydrophobic materials and increased with increasing content of the hydrophilic segment in the polymer. [21][22][23] The presence in the material of inorganic fillers also affected its hydrophilicity. Usually, the materials containing fillers absorbed about 20% less water than foams with the same chemical composition but without fillers.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the amount of absorbed water was lower for the more hydrophobic materials and increased with increasing content of the hydrophilic segment in the polymer. [21][22][23] The presence in the material of inorganic fillers also affected its hydrophilicity. Usually, the materials containing fillers absorbed about 20% less water than foams with the same chemical composition but without fillers.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, since lactones only consist of hydrogen, oxygen and carbon and hence the danger of contamination by added acid ion groups can be kept to minimum, this acidification method has found wide applications in food processing and medicine-related areas. [16][17][18][19][20][21][22] The method has also been applied to engineering processes where continuous or time delayed pH changes in solutions or suspensions are needed to control the release of certain ions at a pre-set rate for either accelerating or retarding the process. 1,2,23-25 Easy removal of the reaction products afterwards (by heating or other methods) and reduction of impurities involved during processing make the method very attractive.…”
Section: Introductionmentioning
confidence: 99%
“…During our investigation of macromolecular syntheses from aldose derivatives such as saccharic and uronic acids,24–31 we found that the novel polyurethanes 12 , 13 , and 14α , prepared from D ‐glucaro‐1,4:6,3‐dilactone ( 8 ), D ‐mannaro‐1,4:6,3‐dilactone ( 9 ), and methyl α‐ D ‐glucofuranosidurono‐6,3‐lactone ( 10α ), respectively, and from hexamethylene diisocyanate ( 3a ) and methyl ( S )‐2,6‐diisocyanatohexanoate ( 3b ) could be hydrolyzed in phosphate buffer solutions to the corresponding saccharide derivatives, diamines, and carbon dioxide at 27 °C more quickly than polyurethanes 15 and 14β , derived from 1,4:3,6‐dianhydro‐ D ‐glucitol ( 11 ) and methyl β‐ D ‐glucofuranosidurono‐6,3‐lactone ( 10β ), respectively:28, 29…”
Section: Introductionmentioning
confidence: 99%